EVALUATION OF WOUND HEALING POTENTIAL OF RUMEX VESICARIUS L. LEAF EXTRACT AND FRACTIONS IN RABBIT - Khan, Imran Ahmad; Sattar, Muzammal; Munawar, Shaukat; Munzoor, zahid; Raza, Muhammad Afiz; fatima, Ghayoor; hannan, abdul; Hannan, abdul (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Rumex vesicarius Linn leaf extract is extensively used in folk medicine for the wound cure in sub-continent, but there is no pharmacological evidence present in support of this practice. The present study was conducted to validate the folkloric use of Rumex vesicarius on experimentally induced excision wounds in rabbits. Phytochemical constituents were also evaluated.Material and Methods: Aqueous and methanol fractions of R.vesicarius leaf extracts were prepared and analysed for the possible presence of major phytochemical classes. A 20% w/v gel of each extract (Methanol, Aqueous) was made using Cabopol 940 in the concentration of 5%. wounds were produced experimentally in normal rabbit’s dorsal region of back under ketamine anesthesia. The decrease in wound size was judged by using a scale. Povidone- Iodine treated group was taken as standard while untreated group was taken as control.Results: Aqueous fraction (200mg/kg) showed 92.34% maximum percentage of wound healing compared to control, while, 79.71% wound healing with methanol fraction (200mg/kg). Both the extracts were found to be statistical significant and comparable to control. Furthermore, wound healing activity was found to be better than standard (Povidone-iodine) treated group which may be attributed to the faster action of the active Phytochemical constituent and their multiple mechanisms.Conclusion: we concluded that R.vesicarius posses good wound healing activity and can be use as alternative medicine for wound care.